Effect of Matricaria aurea essential oils on biofilm development, virulence factors and quorum sensing-dependent genes of Pseudomonas aeruginosa - Qaralleh, Haitham; Mohammed Saghir, Sultan Ayesh; Al-limoun, Muhamad Odeh Atyeh; M. Dmor, Saif; Khleifat, Khaled; Mustafa Al-Ahmad, Basma Ezzat; Al-Omari, Laila; Tabana, Yasser; Mothana, Ramzi Ahmed; M. Al-Yousef, Hanan; M. Alqahtani, Abdulaziz (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Abstract: The emergence of drug-resistant microorganisms presents a substantial global public health threat. The increase in pathogens resistant to commonly prescribed antibiotics underscores the urgent requirement to explore alternative treatment strategies. This study adopts a novel approach by harnessing natural resources, specifically essential oils (EO), to combat bacterial pathogenicity. The primary aim of this research was to analyze the chemical composition of the aerial part of the Matricaria aurea (M. aureas) EO and evaluate its potential for inhibiting quorum sensing (QS) and disrupting biofilm formation in Pseudomonas aeruginosa (P. aeruginosa). The gas chromatography-mass spectrometry (GCMS) analysis unveiled that α-bisabolol oxide A constituted the predominant portion, comprising 64.8% of the total, with β-bisabolene at 6.3% and α-farnesene at 4.8% following closely behind. The antibiofilm efficacy was observed at concentrations of 0.3, 0.15, and 0.08 mg/mL, demonstrating negligible effects on cell viability. Furthermore, the EO from M. aurea effectively inhibited the formation of P. aeruginosa biofilms by diminishing aggregation, hydrophobicity, and swarming motility. Significantly, the EO treatment resulted in a conspicuous decrease in the production of pyocyanin, rhamnolipid, and extracellular polymeric substances (EPS), along with a reduction in the enzymatic activity of protease and chitinase. The EO effectively hindered QS by disrupting QS mechanisms, resulting in a marked decline in the secretion of N-Acyl homoserine lactone (AHL) molecules and the expression of phazA1 and aprA genes. This investigation offers compelling evidence supporting the potential of M. aurea EO as a promising therapeutic candidate for addressing infectious diseases induced by biofilm formation.